“Nilai-nilai Bawah Tanah:” Tinjauan Antropologis Tentang Anarkisme Dalam Paradigma Cultural Studies di Kalangan Anak Muda Kota Makassar - Fajri, Muhammad Faris Al (Universitas Muslim Maros, 2024)
The anarchist punk subculture started with a spirit of resistance, but unfortunately the popular culture that absorbed this subculture has caused it to lose its resistance essence. Despite its spirit, the subculture has been integrated into the very system it previously resisted. This article focuses on the ways in which young people in Makassar City consume